Neuroscience and Psychology: Bridging the Gap between Mind and Brain - Gupta, Pulkita (AG Volumes, 2025)
One issue with the mind-brain divide is the intricate interplay between the fields of neuroscience, clinical psychology and psychiatry, and philosophy of science. Positioning with reference to certain conceptual/philosophical factors is necessary for research in clinical psychiatry and neuroscience. The purpose of this article is to review the diverse literature on the topic of bridging the gap between the mind and the brain. This review highlights the growing precision of theories in behavioural neuroscience, driven by advanced methods of measuring brain activity. Computational models linking neural networks to cognition provide promising insights into brain-mind dynamics and enable prediction of behavioural outcomes. A major challenge remains in constructing comprehensive brain-behaviour models across domains like memory, attention, and mental health. Evidence suggests that the brain functions as a self-regulating system, with self-control networks playing a key role in integrative health. Targeting brain-body imbalances rather than isolated symptoms offers a holistic approach. Though complete solutions remain elusive, emerging findings indicate significant progress in bridging neuroscience and psychology.